2013
DOI: 10.1038/nsmb.2654
|View full text |Cite
|
Sign up to set email alerts
|

Defining the structural relationship between kainate-receptor deactivation and desensitization

Abstract: Desensitization is an important mechanism that curtails the activity of ligand-gated ion-channels (LGICs). Although the structural basis of desensitization is not fully resolved, it is thought to be governed by the physicochemical properties of the bound ligand. Here, we show the importance of an allosteric cation binding pocket in controlling transitions between activated and desensitized states of rat kainate-type (KAR) ionotropic glutamate receptors (iGluRs). Tethering a positive charge to this pocket susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 53 publications
8
61
1
Order By: Relevance
“…The current study clearly shows that (−)-PPDA is a general antagonist that acts on all of the l -glutamate-binding iGluR subunits. A recent study has shown that the Tyr506Cys/Leu768Cys mutations in GluK1 receptors desynchronize receptor activation (Dawe et al, 2013). However, the overall interpretation that (−)-PPDA acts on GluK1 receptors with comparable potency to the GluN1/GluN2A NMDA receptors should remain intact.…”
Section: Resultsmentioning
confidence: 99%
“…The current study clearly shows that (−)-PPDA is a general antagonist that acts on all of the l -glutamate-binding iGluR subunits. A recent study has shown that the Tyr506Cys/Leu768Cys mutations in GluK1 receptors desynchronize receptor activation (Dawe et al, 2013). However, the overall interpretation that (−)-PPDA acts on GluK1 receptors with comparable potency to the GluN1/GluN2A NMDA receptors should remain intact.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, KAR desensitization is thought to be mediated in part by unbinding of sodium prior to that of glutamate, leading to LBD dimer interface rupture (Dawe et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…The LBD binds agonists (including glutamate), antagonists and channel modulators; it is connected to the NTD and TMD layers via peptide linkers. A host of functional and structural data (Mayer, 2006;Traynelis et al, 2010) combined with simulations of individual receptor domains (Arinaminpathy et al, 2006;Bjerrum et al, 2008;Dawe et al, 2013;Dutta et al, 2012;Lau et al, 2011;Lau et al, 2013;Sukumaran et al, 2011;Zhu et al, 2013) has provided a framework of how glutamate-docking to the LBD ‘clamshell’ ultimately triggers ion channel opening followed by receptor deactivation (closure in response to ligand unbinding), or desensitization (closure with ligand bound). Yet, an understanding of how the three domain layers communicate in the intact receptor to ultimately gate the ion channel is currently not well understood.…”
Section: Introductionmentioning
confidence: 99%